Enhancing public works programmes: Sustainable impact through participatory asset creation and digitalisation - Francesco Burchi; Tekalign Gutu Sakketa (German Institute of Development and Sustainability (IDOS), 2025)
Public works programmes (PWPs) are widely used social protection instruments in low- and middle-income countries. Participants carry out temporary, labour-intensive works in exchange for cash or in-kind compensation. The available empirical evidence indicates that these programmes are usually effective in improving outcomes such as food security and earnings in the short term, but these positive effects rarely persist in the long term. Our knowledge of PWPs' effectiveness is, however, incomplete as scholars have mostly examined programme impacts through the wage channel, largely neglecting the skill-development and, especially, the asset channels. PWP participants engage in the construction of assets, such as roads, check dams and sewage systems, that could provide important benefits for the whole community. Without assessing these effects, it is normal to arrive at the general (biased) conclusion that cash transfers (CTs) are always more cost-effective than PWPs. Moreover, the effectiveness of PWPs largely depends on programme design, implementation and context. Based on the existing empirical evidence and our recent fieldwork to analyse Malawi's PWP, this policy brief provides the following policy recommendations for how to enhance the potential of these programmes. Policy-makers should design PWPs to guarantee stable, reliable employment; set wages not higher than market levels but high enough to incentivise participation; ensure transparency in the targeting, possibly by involving communities and at the sametime avoiding elite capture; align the timing of work cycles with local agricultural calendars; and assign tasks in a way that reduces travel burdens,especially for women. Policy-makers should promote active community participation in the identification and maintenance of the assets created through PWPs. Evidence points to the importance of community participation for the implementation of higher quality infrastructure and better long-term maintenance. Only in this way, can these assets provide sustainable benefits not just for programme participants, but for the entire community. Approaches like those used in Ethiopia and Malawi can serve as models to enhance active community participation in the programme cycle. Digitalisation of PWPs (and social protection ingeneral) should be promoted as it offers great advantages, but specific measures should be adopted to avoid their negative consequences: 1. The construction of a digital registry of beneficiaries is a great tool to reach the intended beneficiaries and coordinate the various schemes. Development cooperation actors should provide technical support for the creation and updating of these databases, then leave them in the hands of national institutions. 2. The digitalisation of reporting systems for work activities is likely to improve the accuracy and efficiency of the information reported. To achieve this, it is essential to provide the "digitisers" withproper training. 3. It is important to move from physical cash payments to e-payments, but it is firstly necessary to ensure adequate digital literacy through training. Moreover, to compensate for the impossibility to interact with programme officials at the time of payment, PWPs should include complaint handling points, as is done in India.
Keywords: 320; Public works programmes; social protection; labour market policies; employment; digitalisation; infrastructure; poverty; resilience; participation